O-023 Reperfusion with adapt technique using ACE68 and ACE64 is safe and effective in large vessel occlusions of the anterior circulation – the promise study results. (22nd July 2018) - Navia, P; Schramm, P; Papa, R; Parra, J; Weitz, A; Weber, W; Fiehler, J; Michel, P; Pereira, V; Krings, T; Pierot, L; Gralla, J; et al.
Abstract : Purpose: PROMISE study aimed to observe the safety and effectiveness of Penumbra System (PS) with ACE68 and ACE64 Reperfusion Catheters in patients with acute ischemic stroke (AIS) from large vessel occlusion (LVO), treated with ADAPT (A D irect A spiration F irst P ass T echnique) as front-line treatment. Materials and methods: This was a prospective, single-arm, multicenter study across 20 European centers. Inclusion criteria were anterior circulation LVO within 6 hours of ictus; NIHSS≥2; CT-ASPECTS ≥6; or MR-ASPECTS ≥5. Primary endpoints included success in angiographic revascularization (mTICI 2b-3), and clinical independence (mRS 0–2) at 90 days. Secondary endpoints included safety events, functional improvement at 7–10 days, procedural metrics and quality of life. mTICI scores and safety endpoints were adjudicated by core laboratory and clinical events committee, respectively. Results: A total of 204 patients were enrolled. Median age was 74 [IQR 65–80]. Primary occlusion vessels were 17.2% (35/204) patients with ICA occlusion, 3.9% (8/204) with Carotid T, 60.8% (124/204) with M1% and 18.1% (37/204) with M2. Median baseline CT ASPECT score was 9 [IQR 8–10]. Median baseline and 7–10 day NIHSS scores were 16 [IQR 11–20] and 3 [IQR 1–8], respectively. A reduction of ≤10 points or 7–10 days NIHSS of 0–1 was reported in 67.9% (127/187) patients. Prior to endovascular procedure, IV rtPA was administered in 61.8% (126/204) patients. After PS treatment, 70.3% (142/202) patients achieved mTICI 2b/3. Final revascularization (mTICI 2b/3) was achieved in 93.1% (188/202). Revascularization to mTICI 2 c/3 was achieved 63.9% (129/202). Median time from stroke to revascularization (mTICI 2b/3) was 245.5 min [IQR 192–305]. Median time from puncture to revascularization (mTICI 2b/3) was 31 min [IQR 20–53]. Day-90 mRS of 0–2 was achieved in 61.0% (122/200). In the subgroup analysis by occlusion location, final revascularization (mTICI 2b/3) in the ICA/Carotid T was 95.2% (40/42) and 90 day mRS of 0–2 was achieved in 64.3% (27/42), final revascularization (mTICI 2b/3) in the MCA M1 was 92.7% (114/123) and 90 day mRS of 0–2 was achieved in 57.0% (69/121) and the final revascularization (mTICI 2b/3) in the MCA M2 was 91.9% (34/37) and 90 day mRS of 0–2 was achieved in 70.3% (26/37). There was no significant difference in the safety rates by treatment location. Safety rates were favorable (sICH=2.9%; ENT=1.5%). 90 day morbidity, defined as mRS score (3–5), was observed in 31.5% (63/200). 90 day all cause-mortality was observed in 7.5% (15/200). Device and procedure-related SAEs were reported in 2.0% (4/204) and 4.9% (10/204), respectively. No deaths were device-related. Conclusion: PROMISE study demonstrated safety and efficacy with latest generation of PS Reperfusion Catheters (ACE68/64) in patients with acute ischemic stroke from large vessel occlusion, using ADAPT as front-line treatment. Disclosures: P. Navia: 2; C; Penumbra Inc. P. Schramm: 2; C; Penumbra Inc. R. Papa: None. J. Parra: None. A. Weitz: None. W. Weber: None. J. Fiehler: None. P. Michel: None. V. Pereira: None. T. Krings: None. L. Pierot: None. J. Gralla: None. P. Santalucia: None. T. Lo: None.